2022
DOI: 10.30802/aalas-jaalas-21-000066
|View full text |Cite
|
Sign up to set email alerts
|

Toxigenic Profile of Clostridium perfringens Strains Isolated from Natural Ingredient Laboratory Animal Diets

Abstract: Clostridium perfringens is an anaerobic, gram-positive, spore-forming bacterium that ubiquitously inhabits a wide varietyof natural environments including the gastrointestinal tract of humans and animals. C. perfringens is an opportunistic enteropathogen capable of producing at least 20 different toxins in various combinations. Strains of C. perfringens are currentlycategorized into 7 toxinotypes (A, B, C, D, E, F, and G) based on the presence or absence of 6 typing-toxins (α, β, epsilon, iota, enterotoxin, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 65 publications
(102 reference statements)
0
5
0
Order By: Relevance
“…Although C. perfringens is a signifcant food-borne zoonotic pathogen, very limited microbiological and epidemiological studies have been reported in Bangladesh. In our study, 4 (10.5%) of the type F isolates harbored the enterotoxigenic gene (cpe), which is a potential virulence determinant of C. perfringens for food poisoning in humans [4,5,19,30]. Te low incidence of enterotoxin in chicken may be due to sample source variation as well as the genetic absence of an encoded gene.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…Although C. perfringens is a signifcant food-borne zoonotic pathogen, very limited microbiological and epidemiological studies have been reported in Bangladesh. In our study, 4 (10.5%) of the type F isolates harbored the enterotoxigenic gene (cpe), which is a potential virulence determinant of C. perfringens for food poisoning in humans [4,5,19,30]. Te low incidence of enterotoxin in chicken may be due to sample source variation as well as the genetic absence of an encoded gene.…”
Section: Discussionmentioning
confidence: 77%
“…However, in addition to foodborne intoxication, the enterotoxin producing C. perfringens strains also frequently cause neonatal diarrhea [31]. Furthermore, the enterotoxin gene (cpe) encoded by C. perfringens type F isolates clearly poses the risk of human food-borne intoxication as well as food-borne zoonosis [4,5,32]. Finally, it is recognized that any C. perfringens isolates with alpha toxin and enterotoxin have a signifcant impact on the production of necrotic enteritis in chickens and also cause fatal food-borne enteric disease in humans.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations